Evaluation of the Relationship Between Aniseikonia and Stereopsis Using a New Method - Xu, Lingxian; Liu, Lu; Wu, Huang (Frontiers in Medicine, 2022)
Purpose: To investigate the influence of induced aniseikonia on stereopsis measured by contour-based and random-dot-based stereograms using a new method. Methods: Unlike previous studies in which aniseikonia was induced using magnifiers, which potentially influenced the position of the test symbols in the half-view, here the image was magnified while maintaining each test symbol’s central position within the half-view. A phoropter and two 4K smartphones were used to measure stereopsis in seventeen young adults aged 20-28 years old. Stereopsis was tested using both contour-based and random-dot-based stereograms under overall or meridional aniseikonia with magnifications ranging from 2.5% to 30%. Repeated measures ANOVA was used to evaluate the effect of aniseikonia on stereopsis. Results: Stereopsis decreased with an increase in aniseikonia magnification in the overall, horizontal, and vertical directions. Stereopsis values (log arcsec) increased from 1.29±0.14 at baseline to 2.38±0.16 with 30% overall aniseikonia of contour-based stereograms. In random-dot based stereograms, stereopsis values increased from 1.29±0.16 at baseline to 2.24±0.23 with 22.5% overall aniseikonia. Overall aniseikonia caused a significantly greater impairment on stereopsis as compared with the changes in meridional directions. In contour-based stereograms, vertical aniseikonia had significantly less impact on stereopsis than horizontal aniseikonia of identical magnification. The opposite phenomenon was found in random-dot-based stereograms. Conclusion: Stereopsis decreased with an increase of magnification of induced aniseikonia. Magnifying patterns (overall, horizontal, or vertical) also significantly affected stereopsis. The conflicting impact of meridional aniseikonia on stereopsis measured by contour-based and random-dot-based stereograms may be associated with the uniqueness of the two test systems.